Analisis Pengaruh Online Customer Review dan Online Customer Rating Terhadap Keputusan Pembelian Mahasiswa di Tiktok Shop - Agussalim, Muhammad Ilham; B., Sofyan; Yakub, Rahman; Rusdi, Muhammad (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study was conducted with the aim of determining the extent of the influence of online customer reviews and customer ratings on product purchasing decisions at TikTok Shop, especially among students of the Faculty of Economics and Business, Muhammadiyah University of Sidenreng Rappang. In this study, researchers used a quantitative approach with descriptive methods to obtain an objective picture based on numerical data. Data were collected through distributing questionnaires using a Likert Scale to 75 respondents who had used TikTok Shop as an online shopping platform. To process and analyze the data, multiple linear regression analysis techniques were used with the help of SPSS v.26 software, which allows researchers to test the relationship between variables simultaneously or partially more accurately and systematically. The results showed that online customer reviews have a positive and significant influence on purchasing decisions, with a t-value of 3.100 and a significance of 0.003. Meanwhile, online customer ratings also have a significant effect with a t-value of 4.748 and a significance of 0.000. Both variables simultaneously exerted a significant influence on purchasing decisions, with an F-value of 29.574 and a coefficient of determination (R²) of 0.451. This indicates that 45.1% of the variation in purchasing decisions can be explained by these two variables. This finding confirms that customer reviews and ratings are a primary reference in digital purchasing decisions, particularly on e-commerce-based social media platforms like TikTok Shop.